Description and characterization of studies on telework in the public sector worldwide since covid-19 - Guedes, Marcela Boldrini Gazzani; De Pietri, Patrícia Curbani; Andrade, Alexsandro Luiz de (Brazilian Journal of Production Engineering, 2024)
he Covid-19 pandemic triggered substantial changes in work environments, highlighting telework as a key solution to ensure the continuity of public services. In this context, this article conducted a systematic literature review to analyze the advantages and disadvantages of implementing telework in the public sector worldwide during and after the Covid-19 pandemic. Studies published in the last 5 years (2019 to 2023) were examined to identify patterns and insights on telework in the governmental context. The research highlights the main advantages as improved performance, work-life balance, greater schedule flexibility, and reduced commuting time for public servants. On the other hand, the predominant disadvantages include social isolation, work-life imbalance, and increased working hours. Moreover, significant gaps in the literature on the implementation of telework in the public sector in the post-Covid-19 scenario are revealed. Nevertheless, this study contributes to understanding the effects of telework in the public sector and provides crucial insights for public managers to formulate organizational policies and practices. It also suggests, as future research, in-depth investigations into the potential interference of telework with the work-life balance of public servants.
Keywords: Covid-19; Telework; Impact; Public sector